2020
DOI: 10.1186/s12885-020-07217-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer diagnosis is associated with relative left ventricular hypertrophy and elevated endothelin-1 signaling

Abstract: Background: The survival rates of women with breast cancer have improved significantly over the last four decades due to advances in breast cancer early diagnosis and therapy. However, breast cancer survivors have an increased risk of cardiovascular complications following chemotherapy. While this increased risk of later occurring structural cardiac remodeling and/or dysfunction has largely been attributed to the cardiotoxic effects of breast cancer therapies, the effect of the breast tumor itself on the heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…We recently reported that patients with cancer have relative cardiac hypertrophy prior to receiving cancer treatment, 28 and others have reported abnormal cardiac function at baseline. 29 Thus, patients with cancer may be predisposed to developing CV disease independent of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…We recently reported that patients with cancer have relative cardiac hypertrophy prior to receiving cancer treatment, 28 and others have reported abnormal cardiac function at baseline. 29 Thus, patients with cancer may be predisposed to developing CV disease independent of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Although the gain in running performance was lower in PyMT than in WT mice, it completely counteracted the muscle weakness observed in soleus muscle of PyMT mice. In addition to muscle weakness, cardiovascular disease (CVD) is a common co‐morbidity in patients with cancer, including breast cancer, 36,37 with a 2–6 times higher CVD mortality risk than the general population 36 . Endurance exercise exerts beneficial effects on the whole body and can be used as a powerful tool to enhance cardiac and skeletal muscle function, subsequently reducing the mortality risk and enhancing the quality of life for patients with breast cancer 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Tadic et al's retrospective study using echocardiography examined the strain values in 122 cancer patients before the start of therapy and found a reduction in all three dimensions (16). The probability of systolic impairment is significantly higher in haematooncological diseases (17); however, humoral factors favouring myocardial dysfunction have also been discovered in breast cancer (18). Cancer causes the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%